Frequência de lesões em jogadores de punhobol - Piermann, Everson (2019)
In recent years there has been an increase in the number of competitions and highperformance athletes in Punhobol. With the increase in the number of practitioners, it also triggered an increase in the incidence of injuries of these players. This study aimed to identify the most frequent injuries in this sport and to verify the factors associated with these injuries. A cross – sectional descriptive study was carried out with 42 athletes of both sexes, aged between 18 and 40 years and with practice for more than two years. In the questionnaire, the most frequent injuries were related to the variables: age, sex, anthropometric characteristics, practice time, position, training volume, physical training activities, injury site and external factors that could have caused the injury. A descriptive analysis was performed to characterize the sample and identify the most common type of lesion. It was observed that athletes with a greater frequency of shoulder injuries are concentrated in position 1 and knee in positions 1, 3 and 5. The results found in the study indicate frequency of injuries in 86% of the players and the most frequent injuries are of knee and shoulder, among the most significant variables identified was the training volume.